PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PDAM KOTA MAKASSAR - Murni, Murni (Jurnal Ekonomi Balance, 2011)
The objective of this research is to analyze and to know the influence of organizational culture and leadership behavior toward water management performance in unit installation of PDAM Kota Makassar and to know which variable is the biggest influence to water management performance in unit installation of PDAM Kota Makassar. This study took a sample determined by the census method of the population studied is the number of Employees of Unit Installation IV PDAM Kota Makassar as many as 40 people. The data obtained from the empirical approach are analyzed quantitatively by using simple regression (multiple regression), which is calculated using software (SPSS). The results of research indicate that (1) organizational culture in high category (82,50%) (2) organizational behavior in supporting category (80.00%). The magnitude of the model's predictive power is given by the coefficient of determination symbolized by R2 (R-Square) = 0.611 indicating that the model has a prediction power of 0.611 or about 61.1%. Variations in the rise and fall of employee performance can be explained by the model or influenced by organizational culture variables, and leadership behaviors, while the remaining 38.9% is influenced by other factors not included in the analytical model.